2019
DOI: 10.3390/ijgi8050202
|View full text |Cite
|
Sign up to set email alerts
|

Solving Competitive Location Problems with Social Media Data Based on Customers’ Local Sensitivities

Abstract: Competitive location problems (CLPs) are a crucial business concern. Evaluating customers’ sensitivities to different facility attractions (such as distance and business area) is the premise for solving a CLP. Currently, the development of location-based services facilitates the use of location data for sensitivity evaluations. Most studies based on location data assumed the customers’ sensitivities to be global and constant over space. In this paper, we proposed a new method of using social media data to solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…were obtained. To ensure data quality, the noise-filtering method [ 41 ] was applied to denoise the data (excluding Weibo and advertisements forwarded by users and published by robots). Finally, a total of 20,975 microblog check-in data from 8 November to 7 December 2021, and 20,439 microblog check-in data related to the pandemic from 8 December to 31 December 2021 were retained; some of the Weibo data are selected to display in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…were obtained. To ensure data quality, the noise-filtering method [ 41 ] was applied to denoise the data (excluding Weibo and advertisements forwarded by users and published by robots). Finally, a total of 20,975 microblog check-in data from 8 November to 7 December 2021, and 20,439 microblog check-in data related to the pandemic from 8 December to 31 December 2021 were retained; some of the Weibo data are selected to display in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In the context of retail outlet locations in the fast food industry, both McDonald's and Burger King were shown better off avoiding close location competition if the market area is large enough; but in small market areas, McDonald's would prefer to be located together with Burger King; in contrast, Burger King's profits always increased with greater differentiation (Thomadsen, 2007). Regarding customer's location awareness, Jiang et al (2019) calibrated the Huff model with social media data and found that the customers far from the existing retail agglomerations may be more sensitive to the distance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…GWR is a local modeling tool based on the optimization of global regression models, which complements the global model by providing a set of coefficients for each geographic unit to determine the spatial variability of the observations [53]. The GWR4 software package was used to analyze the indicators:…”
Section: Geographically Weighted Regression (Gwr)mentioning
confidence: 99%